THE ICHTHYOFAUNA OF THE UPPER TEREK AND ITS BASIN - A. S. Abdusamadov; G. M. Abdurahmanov; A. M. Dohtukaeva; L. A. Dudurhanova (Юг России: экология, развитие, 2014)
The work presents an analysis of the ichthyofauna of the Upper Terek, emphasizing different part of the region under consideration. A long-term of skate of sturgeon of larvae is given, characterized the conditions of natural reproduction.